Eurypollinic pollen of the Anacardiaceae differentiates taxa - Tinoco-Domínguez, Eurídice; Castillo-Campos, Gonzalo; Vovides, Andrew P.; Terrazas, Teresa; Palacios-Wassenaar, Olivia (Phytotaxa, 2022)
The pollen morphology of 11 Anacardiaceae species from the Mexican State of Veracruz was studied. Pollen grains were acetolyzed and examined under light and scanning electron microscopy to determine whether their morphological characteristics are useful to differentiate taxa in this family. Photomicrographs were obtained with both types of microscopes and used as the basis for describing the pollen. Pollen descriptions included traits such as shape, the type and number of apertures, exine ornamentation, size of the polar and equatorial axes, and diameter in polar view. Most species have isopolar pollen grains, with tricolpate or tricolporate apertures. Only Pistacia mexicana has pentaporate pollen. Pollen grains exhibit a triradial or radial symmetry in polar view; their shape in equatorial view can be prolate-spheroidal, subprolate, or prolate. The size of axes in equatorial view, diameter in polar view, and the exine ornamentation show distinctive characteristics in each species. However, the most common ornamentation types are microreticulate and microstriate. Ten pollen types were identified based on combinations of traits such as the type and number of apertures, shape in equatorial and polar view, and exine ornamentation. The results confirm that the eurypollinic pollen of Anacardiaceae is valuable for differentiating taxa, highlights the importance of studying pollen morphology and contributes to increasing the knowledge about the pollen morphology of this family in Mexico.